The Role of "Jeng Yah" In Gender Equality In The Cigarette Girl Series - Meisabillah, Billy; Anisa Pujianti, Nisa; Sabilla, Nurul; Siswoyo, Mukarto; Dian Lestari, Aghnia (Asian Journal of Social and Humanities, 2024)
The issue of gender equality is one of the social problems often faced by Indonesian society, especially in the context of issues involving women. This study aims to know and describe the construction of gender equality contained in the series "Cigarette Girl". In this study, the focus is aimed at the journey of "Jeng Yah" in fighting for her rights to achieve gender equality. By analyzing the visual depiction of each scene, the dialogue of the film, and the facial expressions of the players. The research method used to analyze is to use a qualitative approach with the analysis of Robert N. Entman's model framing theory. Entman divides this framing through 4 indicators, namely Define Problem, Diagnose Causes, Make Moral Judgment and Treatment Recommendation. Based on research that has been done, it shows that in the Cigarette Girl series, there is an issue of gender inequality and is felt by the character "Jeng Yah", this happens because there are still gender stereotypes that ultimately make women unable to realize gender equality.